2017
DOI: 10.1681/asn.2016050585
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 and MicroRNA-148 Regulate Parathyroid Hormone Levels in Secondary Hyperparathyroidism

Abstract: Secondary hyperparathyroidism commonly complicates CKD and associates with morbidity and mortality. We profiled microRNA (miRNA) in parathyroid glands from experimental hyperparathyroidism models and patients receiving dialysis and studied the function of specific miRNAs. miRNA deep-sequencing showed that human and rodent parathyroids share similar profiles. Parathyroids from uremic and normal rats segregated on the basis of their miRNA expression profiles, and a similar finding was observed in humans. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…In addition, we demonstrate that the expression levels of miR-148a are positively correlated with PTH. It has been shown that increased levels of miR-148a in rat parathyroid cultures induce an abnormal PTH secretion; importantly, a specific reduction of such miRNA, by using miR-148a antagomiRs, affected PTH secretion in vivo, thus suggesting an association between miR-148a levels and PTH serum concentration [69]. We can hypothesize that the increased circulating expression of miR-148a may have a broad range of effects, thus potentially modifying the secretion of PTH by targeting parathyroid cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrate that the expression levels of miR-148a are positively correlated with PTH. It has been shown that increased levels of miR-148a in rat parathyroid cultures induce an abnormal PTH secretion; importantly, a specific reduction of such miRNA, by using miR-148a antagomiRs, affected PTH secretion in vivo, thus suggesting an association between miR-148a levels and PTH serum concentration [69]. We can hypothesize that the increased circulating expression of miR-148a may have a broad range of effects, thus potentially modifying the secretion of PTH by targeting parathyroid cells as well.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in parathyroid carcinomas identified dysregulated miRNAs when compared to normal parathyroid glands [ 108 , 109 ]. To study the role of miRNAs in SHP, miRNA profiling was performed by deep-sequencing in human parathyroid tissue of end-stage renal disease patients as well as experimental SHP models [ 110 ]. These studies showed that human and rodent parathyroids share similar miRNA profiles.…”
Section: Post-receptor Mechanisms Of Parathyroid Cell Proliferatiomentioning
confidence: 99%
“…The evolutionary conservation of abundant miRNAs in normal parathyroid glands and the regulation of these miRNAs in secondary hyperparathyroidism as well as the effect of specific miRNAs on PTH expression indicate their importance for parathyroid function and the development of secondary hyperparathyroidism. 9 MafB contributes to the increased PTH and cyclin D2 expression in secondary hyperparathyroidism. Future studies may link MafB to the other mechanisms that regulate the parathyroid such as the calcium-sensing receptor, the vitamin D receptor, fibroblast growth factor 23, and miRNAs.…”
Section: See Basic Research On Page 54mentioning
confidence: 99%